Dissociation between blood pressure and heart rate response to hypoxia after bilateral carotid body removal in men with systolic heart failure. Issue 3 (20th December 2013) - Niewinski, Piotr; Janczak, Dariusz; Rucinski, Artur; Tubek, Stanislaw; Engelman, Zoar J.; Jazwiec, Przemyslaw; Banasiak, Waldemar; Sobotka, Paul A.; Hart, Emma C. J.; Paton, Julian F. R.; Ponikowski, Piotr
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Carotid body denervation removes the ventilatory response to acute hypoxia, although haemodynamic responses to acute hypoxia after carotid body removal have not been described conclusively in humans. What is the main finding and its importance? Carotid body removal results in dissociation of heart rate and blood pressure responses to hypoxia in human subjects. While the heart rate response (tachycardia) is maintained, there is a significant attenuation of the blood pressure response (hypertension), which indicates the existence of different sensory afferent pathways in the haemodynamic response to hypoxia that has important clinical implications for this novel therapeutic modality. While the ventilatory response to hypoxia is known to be mediated by the carotid bodies, the origin of the haemodynamic alterations evoked by hypoxia is less certain. Bilateral carotid body removal (CBR) performed to treat congestive heart failure may serve as a model to improve our understanding of haemodynamic responses to hypoxia in humans. We studied six congestive heart failure patients before and 1 month after CBR [median (interquartile range): age, 58.5 (56–61) years old; and ejection fraction, 32 (25–34)%]. Peripheral chemosensitivity (hypoxic ventilatory response) was equated to the slope relating lowest oxygen saturation to highest minute ventilation following exposures to hypoxia. Likewise, systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) slopes were calculated as slopes relating the lowest oxygen saturations to the highest SBP, DBP and HR responses. We found that CBR reduces the hypoxic ventilatory response (∆91%, P < 0.05), SBP (∆71%, P < 0.05) and DBP slopes (∆59%, P = 0.07). In contrast, the HR slope remained unchanged. The dissociation between the blood pressure and HR responses after CBR shows involvement of a different chemoreceptive site(s) maintaining the response to acute hypoxia. We conclude that carotid bodies are responsible for ventilatory and blood pressure responses, while the HR response might be mediated by the aortic bodies. The significant reduction of the blood pressure response to hypoxia after CBR suggests a decrease in sympathetic tone, which is of particular clinical relevance in congestive heart failure.